Representações da realidade brasileira nos primeiros anos da ditadura militar: um diálogo entre Rogério Sganzerla e Rubem Fonseca - Faccio, João Pedro Cardoso (2021)
This work aimed to investigate, through short stories from the first productions of Rubem Fonseca and the film O Bandido da Luz Vermelha, by Rogério Sganzerla, elements of representation of the Brazilian reality in the early years of the Military Dictatorship, in the 1960s. The hypothesis was based on the possibility that the narrative constructions of Fonseca and Sganzerla were formed under the aegis of the “human debasement”, the grotesque. Therefore, this dissertation carried out a journey that sought to understand some of the main modes of fiction based on social reality. Afterwards, the work focused on the biographies of Sganzerla and Fonseca, in favor of identify the main influences and sources of creation. In sequence, there was also an analysis of the situations of Literature and Cinema as arts imported from Europe to Brazilian lands. Finally, and with greater focus, this dissertation executed an analysis of the short stories “Fevereiro ou Março”, “A Coleira do Cão” and “Manhã de Sol”, by Rubem Fonseca, and the film O Bandido da Luz Vermelha, by Rogério Sganzerla, in order to bring together the authors in a dialogue about the representation of the Brazilian reality in their works. The analysis was centered on the marks of the grotesque as an aesthetic category, with a view to verify whether these marks were preponderant in the narrative strategy of the authors and also in Brazilian society, especially from the 1960s. In the corpus of this work, among the main authors who constituted the critical-theoretical basis, are Alfredo Bosi, Antonio Candido, Jean-Claude Bernardet, Karl Erik Schøllhammer, Leyla Perrone Moisés, Muniz Sodré, Raquel Paiva, Paulo Emílio Salles Gomes, Ruben George Oliven and Tânia Pellegrini. The creative complexity of Fonseca and Sganzerla, added to the theme of marginality and the intricate social relations in Brazil justify this work as an effort to make such discussions more critical and profound.